A flavonoid-rich fraction of Euphorbia peplus attenuates hyperglycemia, insulin resistance, and oxidative stress in a type 2 diabetes rat model - Reem S. Alruhaimi; Gomaa Mostafa-Hedeab; Gomaa Mostafa-Hedeab; Maisa Siddiq Abduh; Maisa Siddiq Abduh; Albandari Bin-Ammar; Emad H. M. Hassanein; Emadeldin M. Kamel; Ayman M. Mahmoud; Ayman M. Mahmoud (Frontiers Media S.A., 2023)
Background: Type 2 diabetes (T2D) is a metabolic disorder characterized by insulin resistance (IR) and hyperglycemia. Plants are valuable sources of therapeutic agents for the management of T2D. Euphorbia peplus has been widely used as a traditional medicine for the treatment of various diseases, but its beneficial role in T2D has not been fully explored.Methods: The anti-diabetic efficacy of E. peplus extract (EPE) was studied using rats with T2D induced by high-fat diet (HFD) and streptozotocin (STZ). The diabetic rats received 100, 200, and 400 mg/kg EPE for 4 weeks.Results: Phytochemical fractionation of the aerial parts of E. peplus led to the isolation of seven known flavonoids. Rats with T2D exhibited IR, impaired glucose tolerance, decreased liver hexokinase and glycogen, and upregulated glycogen phosphorylase, glucose-6-phosphatase (G-6-Pase), and fructose-1,6-bisphosphatase (F-1,6-BPase). Treatment with 100, 200, and 400 mg/kg EPE for 4 weeks ameliorated hyperglycemia, IR, liver glycogen, and the activities of carbohydrate-metabolizing enzymes. EPE attenuated dyslipidemia, serum transaminases, tumor necrosis factor (TNF)-α, interleukin (IL)-1β and liver lipid accumulation, nuclear factor (NF)-κB p65, and lipid peroxidation, nitric oxide and enhanced antioxidants. All EPE doses upregulated serum adiponectin and liver peroxisome proliferator-activated receptor γ (PPARγ) in HFD/STZ-induced rats. The isolated flavonoids showed in silico binding affinity toward hexokinase, NF-κB, and PPARγ.Conclusion:E. peplus is rich in flavonoids, and its extract ameliorated IR, hyperglycemia, dyslipidemia, inflammation and redox imbalance, and upregulated adiponectin and PPARγ in rats with T2D.